Examining the Mediating Role of Tax Compliance in the Relationship Between Tax Awareness, Tax Amnesty, Religiosity, and Motor Vehicle Tax Revenue: Evidence from Sibolga City - Nabila Lubis; Marliyah Marliyah; Imsar Imsar (Islamiconomic : Jurnal Ekonomi Islam, 2026)
This study examines the direct and indirect effects of tax awareness, tax amnesty, and religiosity on motor vehicle tax (MVT) revenue through taxpayer compliance in Sibolga City, Indonesia. The study addresses a gap in the local taxation literature by integrating tax awareness, tax amnesty, and religiosity into a single mediation model based on the Theory of Planned Behavior (TPB), with taxpayer compliance serving as the mediating variable. A quantitative research design was employed using survey data collected from 94 registered motor vehicle taxpayers selected through purposive sampling. Data were analyzed using path analysis based on multiple regression to estimate direct, indirect, and total effects among the variables. The findings reveal that tax awareness and religiosity positively and significantly influence taxpayer compliance, whereas tax amnesty exerts a significant negative effect. Taxpayer compliance significantly enhances motor vehicle tax revenue and partially mediates the relationships between tax awareness, tax amnesty, religiosity, and tax revenue. Tax awareness demonstrates the strongest positive total effect on tax revenue, while repeated tax amnesty programs are associated with lower taxpayer compliance and reduced tax revenue, indicating the potential emergence of moral hazard. The study extends the Theory of Planned Behavior by demonstrating the mediating role of taxpayer compliance in explaining the relationship between behavioral and policy-related determinants and local tax revenue. These findings provide practical implications for local governments by emphasizing taxpayer education, strengthening voluntary compliance, improving digital tax services, and carefully evaluating the implementation of recurring tax amnesty programs to achieve sustainable regional tax revenue.